2011
DOI: 10.1103/physrevd.83.062002
|View full text |Cite
|
Sign up to set email alerts
|

Precise response function for the magnetic component of gravitational waves in scalar-tensor gravity

Abstract: The important issue of the magnetic component of gravitational waves (GWs) has been considered in various papers in the literature. From such analyses, it has been found that such a magnetic component becomes particularly important in the high-frequency portion of the frequency range of ground based interferometers for GWs which arises from standard general theory of relativity (GTR). Recently, such a magnetic component has been extended to GWs arising from scalar-tensor gravity (STG) too. After a review of so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(67 citation statements)
references
References 52 publications
(320 reference statements)
2
65
0
Order By: Relevance
“…[1,2] by one of the authors (to whom the exact GEM fields analogy of Sec. 3 was not yet known), it was suggested that the above mapping could be interpreted as arising from the similarity of magnetic tidal forces manifest in relations (132). It seems, however, to be much more related to the analogy based on GEM "vector" fields manifest in Eqs.…”
Section: "Ultra-stationary" Spacetimesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] by one of the authors (to whom the exact GEM fields analogy of Sec. 3 was not yet known), it was suggested that the above mapping could be interpreted as arising from the similarity of magnetic tidal forces manifest in relations (132). It seems, however, to be much more related to the analogy based on GEM "vector" fields manifest in Eqs.…”
Section: "Ultra-stationary" Spacetimesmentioning
confidence: 99%
“…We start in Sec. 2 by revisiting the approach based on tidal tensors introduced in [1] (and partly reviewed in [3]), completing it by extending the formalism to the full gravitational field equations (cast herein as the Einstein field equations, plus the algebraic Bianchi identities). More precisely, through suitable projector techniques, we make a full 1+3 covariant splitting of the latter, obtaining a set of six algebraic equations: four of them involve only the sources, the "gravitoelectric" (E αβ ) and "gravitomagnetic" (H αβ ) tidal tensors, and are formally similar to the Maxwell equations written in this formalism; plus an additional pair of equations that involve the purely spatial curvature (encoded in the tensor F αβ ) and have no electromagnetic analogue.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, labelling the metric perturbation due to the additional GW polarization as h Φ , to the first order approximation of h + , h × and h Φ , the motion of the mirror due to the GW is [57,58,60] …”
Section: Conclusion Remarksmentioning
confidence: 99%
“…Other models where matter action is modified include the bulk viscous stress [35][36][37] and the anisotropic stress [38] or some exotic fluid like Chaplygin gas (CG) [39]. One of the crucial tests to check the viability of extended theories of gravity is the potential detection of gravitational waves [40][41][42].…”
Section: Introductionmentioning
confidence: 99%